The chromosome 14 breakpoint in neoplastic B cells with the t(11;14) translocation involves the immunoglobulin heavy chain locus. - Erikson, J (1984)
We hybridized neoplastic cells from a patient with chromic lymphocytic leukemia of the B-cell type, which carried a reciprocal chromosomal translocation between chromosomes 11 (q13) and 14 (q32) with mouse plasmacytoma cells. The hybrid cells were studied for the presence, rearrangement, and expression of the human immunoglobulin mu chain locus. The results indicate that the expressed mu chain gene is located on the normal chromosome 14, whereas the 14q+ translocation chromosome carries the excluded immunoglobulin constant (C) region mu chain allele (C mu) but does not contain variable (V) region heavy chain genes (VH). Since we found that the heavy chain joining region DNA (JH) of the excluded mu chain gene is on the 14q+ chromosome, we can conclude that the chromosomal break observed in the leukemic cells occurred in a chromosomal region within or 5' of the JH region. With these results, it is logical to postulate that a gene, for which we suggest the name bcl-1, is located on band q13 of chromosome 11 and is activated by its translocation into close proximity with the rearranged heavy chain locus on chromosome 14q+, contributing to the neoplastic transformation of the B cells with the t(11;14) chromosomal translocation.